Haptic Guidance for Extended Range Telepresence - Pérez Arias, Antonia (Karlsruhe Series on Intelligent Sensor-Actuator-Systems / Karlsruher Institut für Technologie, Intelligent Sensor-Actuator-Systems Laboratory, 2013)
A novel navigation assistance for extended range telepresence is presented. The haptic information from the target environment is augmented with guidance commands to assist the user in reaching desired goals in the arbitrarily large target environment from the spatially restricted user environment. Furthermore, a semi-mobile haptic interface was developed, one whose lightweight design and setup configuration atop the user provide for an absolutely safe operation and high force display quality.